A furan-based Lewis-Y-(CD174)-Saccharide mimetic inhibits endothelial functions and In vitro angiogenesis - Sauer, Sandra; Meißner, Tobias; Möhler, Thomas (Advances in clinical and experimental medicine, 2015)
BACKGROUND: Angiogenesis is a fundamental process underlying cancer progression and autoimmune disease. Lewis Y is known as a regulated glycan-structure supporting human endothelial function and angiogenesis. - OBJECTIVES: We hypothesize that Lewis Y based analogues interfere with Lewis Y mediated endothelial functions and angiogenesis. We therefore evaluated the ability of 3, 4-bis [(b-D-galactopyranosyl)osy]-methyl-furan (BGF) a furan-based Lewis-Y saccharide mimetic to inhibit human endothelial adhesion, migration and in vitro angiogenesis. - MATERIAL AND METHODS: The ability of BGF and additional furan-based saccharide-mimetics was investigated to inhibit adhesion and migration of human bone marrow endothelial cells (HBMEC). Influence of BGF was tested on a multicelluar in vitro - angiogenesis assay in the presence of VEGF. - RESULTS: BGF significantly inhibited HBMEC adhesion and migration stimulated by TNF-alpha by up to 70%. The anti-adhesive effect of BGF was particularly evident when HBMEC adhesion and migration was tested on collagen as extracellular matrix with weaker effect when laminin and fibronectin were used as an extracellular matrix. BGF was ineffective when HBMEC were stimulated with VEGF. The inhibition of endothelial function translated into a significant inhibitory effect of BGF in the multicellular in vitro angiogenesis-assay. BGF reduced the angiogenesis index compared to the positive controls by 32%. - CONCLUSIONS: We identified the ability of the furan-based Lewis Y saccharide mimetic BGF as a specific modulator of TNF-alpha activated endothelial function and in vitro angiogenesis. BGF and other related glycan analogues should further be explored for their ability to down modulate endothelial activation in TNF-alpha driven pathophysiologic conditions in autoimmune disease and cancer indications.
Gesehen am 16.06.2020